KEPLOK DAN ALOK DALAM KLENENGAN KARAWITAN GAYA SURAKARTA - Indah Tri Suryani; Wahyu Thoyyib Pambayun (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2025)
This paper reveals the expressionist aesthetic problem of keplok alok in Surakarta style karawitan based on the forming factors of musical expressionist aesthetics. Data collection is obtained by means of literature studies, observations, and interviews. Using qualitative research methods with descriptive research types and the theoretical foundation of Theodore Adorno (1948) that the factors forming musical expressionist aesthetics, namely emotion, material formation, contrast, and darkness. In depth, the definition of aesthetics is not only a matter of beauty but comes to the problem of taste. A taste will produce an expression which can produce an impression or character in the presentation of gending karawitan. Keplok and alok are the main musical elements in the smallest character and are not standard, but have a major influence on the taste, beauty, character, purpose or expression created from a gending dish.